Optimalisasi Keuntungan pada Perusahaan Keripik Sanjai Mintuo dengan Metode Branch and Bound - Dythia wulandari; Yusmet Rizal (Journal of Mathematics UNP, 2020)
Abstract— The purpose of the company is looking for profit or benefit as much as possible with the existing restrictions, one which of the lack in management is the terms of production (over product inventory or  the products do not consumer market demand). Optimal use of raw ingredients is needed to maximize the amount of production that will the produce greater profits. The purpose of this study was to determine the shape of the model and the results of production at the Sanjai Mintuo company using the branch and bound method. The branch and bound method is a method used to found the integer programs. In the Sanjai Mintuo chips company, the optimal production results are 209 sanjai bargain, 154 Lado Red Sanjai, 133 Green Sanjai Lado, 117 packages of corn flavour with optimal benefit for production (for 3 days) Rp. 5.862.907. Keywords—branch and bound method, optimization, sanjai